2011
DOI: 10.1143/jjap.50.076502
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Film Chemical Mechanical Polishing Using MnO2 Slurry

Abstract: An analysis is presented of the use of the spectrum of near vertical cosmic ray muons in deriving the energy spectrum of primary cosmic ray nucleons. The model used for high energy interactions in the atmosphere is that derived from ISR measurements, which cover the range 2.5 x 102-1.5 x IO3 GeV, and their extrapolation. The effect of variations from straightforward extrapolation is also examined.The nucleon spectrum is used to derive alternative spectra of primary nuclei for different assumptions about the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The Mohs hardness of MnO 2 is in the range of 6-7. [20][21][22] The Mohs hardness of fumed silica (SiO 2 ) is in the range of 6.5-7.0. 23) Thus, MnO 2 and fumed silica have similar hardness.…”
Section: Resultsmentioning
confidence: 99%
“…The Mohs hardness of MnO 2 is in the range of 6-7. [20][21][22] The Mohs hardness of fumed silica (SiO 2 ) is in the range of 6.5-7.0. 23) Thus, MnO 2 and fumed silica have similar hardness.…”
Section: Resultsmentioning
confidence: 99%
“…As manganese oxide has been revealed to have some interesting characteristics, several corresponding studies have been performed. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Some of these studies reported that manganese oxide slurry polishes several materials such as tungsten, copper, SiO 2 , and low dielectric constant materials.…”
Section: Introductionmentioning
confidence: 99%
“…One of these is manganese oxide slurry. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] We have performed previous studies of manganese oxide slurries and their application to CMP, [18][19][20][21][22] and established that MnO 2 abrasive polishes tungsten film without etching solution 19,20,24) and MnO 2 is also able to polish SiO 2 film faster than the conventional fumed silica slurry even without pad conditioning. [21][22][23][24] We further clarified that Mn 2 O 3 is capable of polishing SiO 2 film around 4 times faster than the conventional fumed silica slurry even without pad conditioning and is easy to remanufacture.…”
Section: Introductionmentioning
confidence: 99%